Banalitas Kebohongan Manusia Era Post-Truth. Sebuah Rekonstruksi Nalar dengan Analisis Kritis Mary Douglas danJürgen Habermas - Kurniawan, Trio (Perspektif, 2018)
The post-truth era presents the banality of hoax with populism as its main arm. Hoax affects the social order of the society in such a way that it often creates an outcry that makes distrust among the people. Internet has become the most proper media for disseminating hoax information. Group and Grid theory of Mary Douglas will be used to analyze this phenomena. Critical theory of Jürgen Habermas will be used as a ‘scalpel’ to reconstruct human common sense in this post-truth era in order to promote a better social order in the society.